Design of a wideband terahertz absorber composed of graphene patches. Issue 5 (1st October 2019) - Karimi, Parisa; Maddahali, Mohsen; Bakhtafrouz, Ahmad; Shahabadi, Mahmoud
Abstract : Here, the design of a wideband absorber operating at terahertz frequencies is presented. The design is based on an analytical circuit model of graphene arrays of rectangular patches obtained from the presented circuit model of graphene arrays of disks. A recently proposed method is generalised for the design of wideband absorbers at higher frequencies. The bandwidth is increased by correct tuning of the input impedance for a structure composed of two layers of graphene arrays and a metal‐backed dielectric layer. Using two‐layer graphene arrays, the authors decrease the slope of the imaginary part of the input impedance to increase the bandwidth. The designed absorber works at a frequency of 4THz and has a higher bandwidth of about 30% with respect to the predicted bandwidth by the recently proposed method. The structure is analysed by a transmission‐line formulation method. Consequently, it is demonstrated that the 90% ‐absorption bandwidth can be increased up to 80% of the central frequency.